(3GdHjWQIs - (3eLghds
(3ChdgG (B:s
(3eHJhQ GdChd hChd eG LGA ajg EPG JMQc hGcKQ eG JLOgPg GdYdg EPG GYJdaJ GdOhGH GdNVQ hGdPjf jQhf Cfge jShhfg H(B'(3ONGd GjOjge s
(3BNQgG (B:s
(3eHJhQ GdCNQ GdbhdfL hGdSYa hGdcdjJjf , Ccd GdOadi GdQWhHI JSjd ef GdCfa s
(3GdfSNI HgG MhGTs
(3fSNI KGfjI ef GdLRA GdKGfi ef GdeJbOeI hgj CUdgG Ydi eG jHOh jJbOegG agQS eaUd dCHhGH GdLRAs
(3hJTJed Ydi HYV GhQGb HNW GMOKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B37 s
Keywords: (3GdWHs